Seroprevalence of Chlamydia abortus in camel in the western region of Libya - Elzlitne, Rabia; Elhafi, Giuma (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The present study was primarily undertaken to determine the seroprevalnace of Chlamidya abortus infection in the Libyan camel (Camelus dromedarius). Materials and methods: Serological tests for C. abortus antibodies were conducted with 245 camels (205 females and 40 males) in different localities in the western region of Libya. Animals varied in age from <1 to 20 years and were sampled randomly from both housed and nomadic herds. From each animal, 10 mL blood sample was collected and sera were separated. Antibodies in the sera against C. abortus were detected using an indirect enzyme-linked immunosorbent assay (ELISA). Results: Results of this study showed that out of the 245 camels tested for anti-chlamydia antibodies, 30 were found positive giving an overall prevalence of 12.25%. The seroprevalence of chlamydiosis was 2 folds higher in females (14.00%) as compared to males (5.00%). Conclusion: The present findings signify the C. abortus as a potential agent to cause abortion in Libyan camel (C. dromedarius). Besides, the persons who handle camels in Libya are at risk of infecting with C. abortus. http://doi.org/10.5455/javar.2016.c151